The Effectiveness of Land Redistribution Programs in Increasing Public welfare - Veramitha Sari, Indah; Winjaya Laksana, Andri (Jurnal Konstatering, 2025)
This study aims to analyze: 1) The effectiveness of the implementation of the land redistribution program in improving the welfare of the people in Kutai Kartanegara. 2) Obstacles and solutions in the implementation of the land redistribution program in improving the welfare of the people in Kutai Kartanegara. This type of research is empirical legal research. The approach method in this research is a qualitative approach. The types of data in this research are primary and secondary. Primary data collection through observation and interviews while secondary data uses library techniques (study document). The analysis in this study is descriptive. The results of the study concluded: 1) The effectiveness of the implementation of the land redistribution program in improving the welfare of the people in Kutai Kartanegara has been effective in realizing the objectives of agrarian reform, namely equal distribution of land ownership and improving community welfare. If analyzed based on Soerjono Soekanto's theory of legal effectiveness, the success of this program is supported by clear legal factors, committed law enforcement, and adequate implementation facilities. In addition, community participation in managing land productively and the cultural values of mutual cooperation also strengthen the effectiveness of program implementation. 2) Obstacles in the implementation of the land redistribution program consist of legal, technical, social, and institutional obstacles. Legal obstacles arise due to the lack of synchronization of regulations and data between agencies, while technical and social obstacles are caused by limited resources, geographical conditions, and minimal community assistance after the redistribution. Solutions that need to be implemented include strengthening coordination through the Agrarian Reform Task Force (GTRA), accelerating the digitalization of land data, and improving coaching and empowerment programs for beneficiaries. The implementation of PP Number 62 of 2023 is key to ensuring a more focused and uniform implementation.